Small but not ephemeral: newly discovered species of Aphelinidae and Trichogrammatidae (Insecta: Hymenoptera: Chalcidoidea) from Eocene amber. (28th April 2015) - BURKS, ROGER A.; HERATY, JOHN M.; PINTO, JOHN D.; GRIMALDI, DAVID
Abstract New species of fossil Aphelinidae and Trichogrammatidae are described from middle Eocene (Lutetian) Baltic amber (41.3–47.8 Ma). A new subfamily, two new genera and three new species of Aphelinidae are described, with comments on their placement: Phtuaria fimbriaegen.n., sp.n. in Phtuariinae subf.n., Glaesaphytis interregnigen.n., sp.n. and Centrodora brevispinaesp.n. These represent the first described true fossil Aphelinidae. Four new species of Trichogrammatidae are described: Mirufens illusionissp.n., Palaeogramma eosgen.n., sp.n., Pterandrophysalis plasmanssp.n. and Szelenyia terebraesp.n., thus expanding our knowledge of fossil Trichogrammatidae beyond the single previously described species. The presence of recognizable extant genera of Aphelinidae and Trichogrammatidae in the Eocene suggests that the morphology of these genera has been relatively invariant despite highly variable conditions during and since the Eocene. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:E9AD60B6‐3D56‐4E74‐AA54‐F7B91F4FDC79.